Image and Reputation Damage. The Honour Council for Architecture and Applied Art (Bulletin KNOB, 2014)
Immediately after the Second World War, the opposites of right and wrong strongly influenced the view of what happened in the architectural profession during the German occupation. In order to understand the reception of architecture and National Socialism in the post-war Netherlands, it is useful to trace how this image was formed. The Honour Council for Architecture and Applied Art, which was established after the Second World War in order to bring ‘wrong’ architects to justice, is a good point to start.When the war ended, those architects could face various forms of justice, depending on their behaviour during the occupation. Architects that had committed crimes would be tried before a court of special criminal law, just like other citizens. To that end, the Dutch government in exile in London had issued the Special Criminal Law Decree, in December 1943, and the Tribunal Decree, in September 1944. In addition to that, Honour Councils were established for various occupational groups that were intended to take disciplinary measures against those who had acted reprehensibly in the practising of their profession during the war, even if they had not actually committed crimes as defined by law. One of these councils was the Honour Council for Architecture.One problem was that initially there was no legal ground for a purge among artists in the Netherlands: the Purging Decree of January 1944, issued by the Dutch government in London, only concerned civil servants. And although no one worried too much about this when the Honour Councils for the Arts were established, this omission would considerably hamper the councils later on, especially when it came to enforcing the measures imposed upon individuals. It wasn’t until 5 April 1946 that the Artists Purging Law came into effect, giving the councils the legal authority to issue verdicts. In December of the same year, the Honour Council for Architecture had already stopped its activities, meaning that, in the end, it had only been able to perform its duties on a sound legal basis for little more than six months.Although in hindsight the work of the Honour Councils for the Arts was generally regarded a failure, their verdicts have greatly influenced the image of the architects concerned. The reputations of an entire generation of architects were either saved or destroyed. During the first few decades after the Second World War, convictions by the Honour Council were not lightly forgotten by fellow architects. The consequences of the verdicts from the Honour Council therefore still influence the evaluation of the work of these convicted architects.